Microsatellite analysis generates hope for sustainability of two dwindling camel populations of Rajasthan - SHARMA, REKHA; SHARMA, HIMANI; SHARMA, PRIYANKA; AHLAWAT, SONIKA; MEHTA, S C; TANTIA, M S (The Indian Journal of Animal Sciences, 2018)
The declining camel population in the country is a matter of major concern for the conservation biologist, policy makers and the state governments. In the present study, diversity status of two declining camel populations of India, viz. Mewari and Jalori was established using 25 microsatellite markers. Analysis of genotype data showed that sufficient amount of genetic variation is maintained in these camel populations. A total of 174 alleles were detected in Mewari and 155 in Jalori camel. Highest number of alleles (17) was observed at CMS58 locus in Mewari and CVRL01 and YWLL08 in Jalori camel. The mean observed number and effective number of alleles across all the loci was 9.67±0.94, 4.52±0.46 and 8.61±0.86, 4.41±0.46 for Mewari and Jalori, respectively. Difference in the observed and expected number of alleles in both the populations suggested presence of several low frequency alleles in these populations. In accordance with high allelic diversity, estimate of observed heterozygosity (Ho) was also high (0.68±0.04 and 0.71±0.04 for Mewari and Jalori, respectively). Nine loci in Mewari and 10 in Jalori deviated from HWE. Observed and expected heterozygosity were of similar magnitude and correspondingly FIS analysis identified no significant heterozygote deficiency. Both the populations did not suffer from any recent genetic bottleneck. Distinctness of two populations was supported by the observation that all the Jalori and Mewari animals except one were assigned to their own populations. Bayesian approach also concluded that the two populations were distinct. Abundant genetic variation maintained in these camel populations provides important inputs for the decision-making process regarding their conservation and improvement.